Peran Self-Compassion Terhadap Depresi Pada Mahasiswa Dengan Resiliensi Sebagai Mediator (Jurnal Ilmiah Psikologi MIND SET, 2024)
The increasing responsibilities and demands faced by university students often make them vulnerable to depressive symptoms. A study was conducted to explore how self-compassion affects depressive symptoms among students, with resilience playing a mediating role. The study involved 200 university students (164 females) from a university in Jakarta. Mediation analysis was performed using the MedMod module with bootstrap estimation method, using 1000 resamples to estimate mediation effects and establish 95% confidence intervals. The results indicated that resilience partially mediated the relationship between self-compassion and depression. Students with higher self-compassion tend to be less self-critical when facing failure, perceive difficult situations as something that can happen to anyone, and maintain a balanced perspective without overgeneralizing. These characteristics of self-compassion enhance resilience, which in turn contributes to reducing depressive symptoms during challenging times.